2018
DOI: 10.1109/tvcg.2017.2666150
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Classification and Optimization for Multi-Modal Rendering of Real-World Scenes

Abstract: We present a novel algorithm to generate virtual acoustic effects in captured 3D models of real-world scenes for multimodal augmented reality. We leverage recent advances in 3D scene reconstruction in order to automatically compute acoustic material properties. Our technique consists of a two-step procedure that first applies a convolutional neural network (CNN) to estimate the acoustic material properties, including frequency-dependent absorption coefficients, that are used for interactive sound propagation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…Analytical gradients can significantly accelerate the optimization process. With similar optimization objectives, it was shown that additional gradient information can boost the speed by a factor of over ten times [33,50]. The speed gain shown by Li et al [33] is impressive, and we further improve the accuracy and speed of the formulation.…”
Section: Related Workmentioning
confidence: 64%
See 2 more Smart Citations
“…Analytical gradients can significantly accelerate the optimization process. With similar optimization objectives, it was shown that additional gradient information can boost the speed by a factor of over ten times [33,50]. The speed gain shown by Li et al [33] is impressive, and we further improve the accuracy and speed of the formulation.…”
Section: Related Workmentioning
confidence: 64%
“…We also achieve faster optimization speed. Note that the input audio to our method is already noisy and reverberant, whereas [33] [50]. In the highlighted region, we are able to better reproduce the fast decay in the highfrequency range, closely matching the recorded sound.…”
Section: Comparisonsmentioning
confidence: 72%
See 1 more Smart Citation
“…We now estimate the acoustic material from the reconstructed image using the widely used CNN to predict visual appearance. As mentioned in [7], [8], estimating the visual aspect of an image can be considered as a kind of semantic segmentation. In general, semantic segmentation tasks classify and separate various objects in the scene.…”
Section: B Acoustic Materials Estimationmentioning
confidence: 99%
“…Recent SSL papers considering reflection [5] and diffraction [6] only use the 3-D geometry of indoor rooms for the real-time processing, without taking into account acoustic material information. Because accurate estimation of acoustic material is difficult, several approaches [7], [8] were proposed for the approximate estimation using visual appearance without sound information. These methods use RGB or RGB-D images to perform the acoustic material estimation and the 3-D reconstructions.…”
Section: Introductionmentioning
confidence: 99%